CLASIFICAREA GRUPURILOR ȚINTĂ PENTRU POLITICILE GUVERNAMENTALE DE PROTECȚIE SOCIALĂ - Coţofan, Denis (CEP USM, 2023)
The article approaches social protection from the perspective of which groups of this protection falls on. The specialized literature does not contain a multilateral approach to this subject, in fact it generates an increased interest in developing a new vision and cataloging the target groups on which the village policy is applied in the social protection field. At the same time, in order to generate a viable formulation, the article will examine the functions of social protection and address the concept of social risk, as a result, will be proposed a new cataloging of people able to benefit from social protection provided by the Republic of Moldova.
CLASSIFICATION OF TARGET GROUPS FOR GOVERNMENT POLICIES OF SOCIAL PROTECTION
COȚOFAN, Denis. Clasificarea grupurilor țintă pentru politicile guvernamentale de protecție socială. In: Teoria și practica administrării publice: materiale ale conferinței ştiințifico-practice internaționale, ediţia a 27-a, 19 mai 2023, Chişinău. Chişinău: Centrul Editorial-Poligrafic al USM, 2023, pp. 84-90.
Keywords: social protection; social protection functions; target group; social risk; social assistance; social insurance; allowance; aid